Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.4102/phcfm.v15i1.3879
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring empowers adolescents to take responsibility of diabetes management

Abstract: Background: Managing diabetes is especially challenging for adolescents, and they often struggle to believe they can manage the condition. Illness perception has been widely associated with better diabetes management outcomes, but the influence of continuous glucose monitoring (CGM) on adolescents has been largely neglected.Aim: The study aimed to explore the illness perception of a group of adolescents living with type 1 diabetes (T1D) using CGM.Setting: The study was conducted at a medical centre that provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Adjusting to diabetes happens over time, just as developing an identity does. Oris and colleagues (32) identified four phases of identity development, which was evident in the adolescent participants in the various studies reviewed here: engulfment was evident in all groups as they reported being overwhelmed by the initial diagnosis (6,29,30); rejection of diabetes as part of their lives was evident in the uncontrolled group (6); acceptance was seen in the wellcontrolled and CGM groups (29,30); and enrichment was seen also in the well-controlled and CGM groups (29,30). The differences in identity development among the well-controlled and uncontrolled groups imply that teaching adolescents to think more like the wellcontrolled group could be beneficial, and that the use of CGM empowers not only diabetes management but potentially also identity development in adolescents living with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Adjusting to diabetes happens over time, just as developing an identity does. Oris and colleagues (32) identified four phases of identity development, which was evident in the adolescent participants in the various studies reviewed here: engulfment was evident in all groups as they reported being overwhelmed by the initial diagnosis (6,29,30); rejection of diabetes as part of their lives was evident in the uncontrolled group (6); acceptance was seen in the wellcontrolled and CGM groups (29,30); and enrichment was seen also in the well-controlled and CGM groups (29,30). The differences in identity development among the well-controlled and uncontrolled groups imply that teaching adolescents to think more like the wellcontrolled group could be beneficial, and that the use of CGM empowers not only diabetes management but potentially also identity development in adolescents living with type 1 diabetes.…”
Section: Discussionmentioning
confidence: 80%
“…The effect of beliefs about the consequences of diabetes, as well as beliefs in its control, underlaid themes 3 and 4 and the discussion above. The differences in personal control are important to note: those who managed diabetes well and those using CGM were empowered by positive feedback, which gave them confidence in managing the condition (29,30), even when they struggled. Adolescents in these groups held strong beliefs about personal control, although the control of treatment may not have been effective.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations